Inequality, Resilience, and Climate Change Adaptation: A Socio-Economic Study of the Coastal Communities in Indramayu, West Java - Ilahi, Fadhli Fauzan; Khoirunnisa, Nina; Rahmat, Hansa Nabila; Asheva, Alfath Zaidanaufal (UIN Sunan Gunung Djati Bandung, 2024)
This study explores the socio-economic impacts of climate change on coastal communities in Indramayu, Indonesia, focusing on livelihood changes, social mobility, and local adaptation processes. Amid growing global concern over climate vulnerabilities, this research underscores the importance of addressing human dimensions in climate responses. Employing a qualitative approach, data were collected through online observations and literature reviews, then analyzed thematically to identify recurring patterns and adaptive behaviors. The findings reveal that climate change has severely affected traditional economic sectors—especially fisheries—triggering income diversification through microenterprises and nature-based tourism. Social solidarity, informal leadership, and collective environmental actions such as mangrove rehabilitation emerged as key components of community resilience. Nonetheless, disparities in access to information, resources, and policy support hinder equitable adaptation, particularly for marginalized groups like small-scale fishers and female-headed households. This research contributes to the literature on climate adaptation by illustrating how socio-economic transformation is both a necessity and consequence of environmental stress. It calls for inclusive, evidence-informed policy interventions that empower communities and reduce adaptation inequality. The originality of this study lies in its emphasis on socio-economic adaptation processes within Indonesian coastal communities—an area underrepresented in existing scholarship.​